2019
DOI: 10.1177/0885328218825177
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenesis of 3D printed macro-pore size biphasic calcium phosphate scaffold in rabbit calvaria

Abstract: To investigate the osteogenesis of macro-pore sized bone scaffolds, biphasic calcium phosphate scaffolds with accurately controlled macro-pore size (0.8, 1.2, and 1.6 mm) and identical porosity of 70% were fabricated by the 3D printing technology. Eight New Zealand rabbits were selected in the present study, while four 8-mm-diameter calvarial defects were created in each rabbit to place BCP scaffolds with different macro-pore size. The harvested specimens of four and eight weeks were used to evaluate the bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 50 publications
(70 reference statements)
2
16
0
Order By: Relevance
“…Ilea et al [ 17 ] showed in their study that titanium scaffolds with pores of 800 nm in diameter exhibited better osseointegration than scaffolds with pores of 1000 nm. Similar results were obtained by Liu et al [ 18 ]. The authors studied osteogenesis of 3D printed calcium phosphate bone scaffolds made with 70% porosity and a large pore size of 0.8, 1.2, and 1.6 mm.…”
Section: Resultssupporting
confidence: 92%
“…Ilea et al [ 17 ] showed in their study that titanium scaffolds with pores of 800 nm in diameter exhibited better osseointegration than scaffolds with pores of 1000 nm. Similar results were obtained by Liu et al [ 18 ]. The authors studied osteogenesis of 3D printed calcium phosphate bone scaffolds made with 70% porosity and a large pore size of 0.8, 1.2, and 1.6 mm.…”
Section: Resultssupporting
confidence: 92%
“…With the improvement of computeraided design/computer-aided manufacturing (CAD/CAM) technologies it has been feasible to analyze the bone deficiency of a patient on a 3D-CT scan and to create bone grafts that fit perfectly into the receiving site (Mangano et al, 2015b;Luongo et al, 2016;Raymond et al, 2018). Several techniques have been used to produce three dimensional scaffolds [e.g., inkjet printing, stereo lithography, fused deposition modeling, and selective laser sintering (Bose et al, 2013;Hwang et al, 2017;Liu et al, 2019;Chung et al, 2020)]. These techniques allow the creation of solid constructs with an excellent pore interconnectivity, high biocompatibility, capabilities of maintaining space and, for bone regeneration procedures, they seem to be able to provide greater osteoconductivity (Carrel et al, 2016;Hwang et al, 2017;Raymond et al, 2018;Kim et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of 3D printing technology allowed the precise control of pore size while the morphology within the printed PCL and composite scaffolds was accomplished. As it is known, the natural bone consists of trabecular bone encircled by cortical bone, which creates a porous environment characterized by 50-90% porosity and 1 mm pore size [37,38]. Only when the microenvironment of the trabecular bone in respect of the respective cell-cell/cell-matrix interaction [38] (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…As it is known, the natural bone consists of trabecular bone encircled by cortical bone, which creates a porous environment characterized by 50-90% porosity and 1 mm pore size [37,38]. Only when the microenvironment of the trabecular bone in respect of the respective cell-cell/cell-matrix interaction [38] (Fig. 3) is imitated, a bone scaffold can be considered ideal.…”
Section: Discussionmentioning
confidence: 99%